PENGEMBANGAN PANGBON SEBAGAI MEDIA STORYTELLING BAGI ANAK USIA DINI DI TAMAN KANAK-KANAK - Sri Yunimar Ningsih; Desi Karmila; Miptahul Jannah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop a learning medium in the form of a puppet stage as a storytelling tool for early childhood in kindergarten. Storytelling is an effective learning method for stimulating children's language development, imagination, and social and emotional values. However, the lack of engaging and interactive media often becomes an obstacle in applying this method in early childhood education settings. This research employs the Research and Development (R&D) method using the development model, adapted up to the limited product trial phase. The results of the study indicate that the developed puppet stage is capable of increasing children's interest and participation in storytelling activities. Evaluations from teachers and children show that this medium is engaging, easy to use, and effective in supporting the achievement of learning objectives. Thus, the puppet stage medium can be considered an innovative alternative for storytelling activities in kindergarten.